Korelasi antara Pola Ikatan Pembuluh dengan Sifat Fisis dan Mekanis Tiga Jenis Bambu (Correlation of Vascular Bundle Pattern with Physical and Mechanical Properties of Three Bamboo Species) - Nani Nuriyatin; Surjono Surjokusumo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
The physical and mechanical properties of three species of bamboo, namely Dendrocalamus giganteus, Dendrocalamus asper, and Gigantochloa apus were investigated in relation to its vascular bundle pattern. As physical and mechanical properties, specific gravity, modulus of rupture (MOR), modulus of elasticity (MOE), compressive strength parallel to grain and tension strength parallel to grain were determined, and the vascular bundle pattern was evaluated by method according to Grosser and Liese (1971). The relationship between physical and mechanical properties with the vessel bundle pattern was analyzed by regression with dummy variables. Pattern combination of vessel bundle was found on G. apus and D. asper, while D. giganteus has a single pattern of vessel bundle type. The difference of vascular bundle pattern did not contributed to the physical and mechanical properties of bamboo investigated, except for MOR. The difference species of bamboo and vertical position of samples contribute to the different value of compressive strength parallel to grain, whereas tension strength was only affected by bamboo species